PERKEMBANGAN FRUIT SET TANDAN KELAPA SAWIT (Elaeis guineensis Jacq.) DENGAN PERLAKUAN BERBAGAI FORMULA HARA - Candra Ginting; Muslim Panjaitan (AGROISTA : Jurnal Agroteknologi, 2018)
The production of bunches fruit set in the palm oil is influenced by several factors such as water, nutrients and pollination. Sex ratio of an oil palm tree is affected by both genetic and environmental factors. Male and female inflorescences development are influenced by nutrients. The research was conducted with seven treatments nutrient formula for seventy stand to know fruit set development of oil palm. The number of male and female inflorescences have been calculated three months after fertilizer application. Increasing in male and female inflorescences as effect of several treatments of nutrient formula. Change in sex ratios to average 0,4 after treatments from 0.5 before. Productivity potential of fresh fruit bunch in communal or population increased with application of nutrient formula. Keywords: fruit set, sex ratio, male and female inflorescences, nutrient formula